(untitled) (Academic Journal of International University of Erbil, 2025)
This study investigates the factors influencing internal audit effectiveness within the public sector of Erbil. The primary focus is on management support, organizational settings, and auditor development, all of which are considered critical for improving audit quality. A quantitative research design was employed, using a structured questionnaire distributed to internal auditors and management personnel in public organizations across Erbil. The results, analyzed through Exploratory Factor Analysis (EFA), revealed five key factors impacting audit effectiveness: auditor development and technology, managerial support and guidance, managerial decision-making, auditor autonomy, and internal audit policies. Notably, management support emerged as the most significant determinant of effective audits. These findings highlight the importance of fostering an environment of managerial engagement, professional development, and auditor independence to enhance transparency and governance in the public sector. The study contributes valuable insights for policymakers seeking to improve audit practices in developing regions and suggests areas for future research, including expanding the scope to other regions and exploring the role of technology in audit processes.